Assessing the Ecotourism Potential of Birdwatching in Tebet Eco Park, an Urban Green Space in South Jakarta, Indonesia - Nismara, Muhammad Inas; Oktovianus; Sitanggang, Igras Vigran Antonio (Journal of Tourism Sustainability, 2025)
As one of the world's megadiverse countries, Indonesia holds vast potential for developing nature-based tourism, particularly avitourism. This study examines the birdwatching ecotourism potential of Tebet Eco Park, an urban green space in South Jakarta, by analyzing bird species' diversity, richness, dominance, and evenness within the park. Bird surveys were conducted from October to December 2024 using standardized observation methods along designated transects. A total of 24 bird species from 21 families were recorded. The Shannon-Wiener diversity index (H' = 2.46) and the Margalef richness index (R = 3.44) indicate moderate species diversity and community stability. Streptopelia chinensis and Pycnonotus aurigaster were the most dominant species, while Zosterops melanurus and Psittacula alexandri were identified as species of conservation concern. Several birds, such as Nectarinia jugularis, were noted for their colorful plumage or distinctive vocalizations, making them attractive for recreational birdwatching. The findings demonstrate that Tebet Eco Park has strong potential to be developed as a sustainable, accessible, and educational birdwatching ecotourism destination within an urban setting.